Tantangan Perioperatif pada Pasien Penyakit Jantung Rematik yang menjalani Prosedur Seksio Sesarea – Laporan Kasus - Hotabilardus, Nusi A; Masjkur, Diana; Anggraeni, Novita (Journal of Medicine and Health, 2025)
Rheumatic heart disease (RHD) is a major contributor to maternal morbidity and mortality in developing countries, including Indonesia. Severe preeclampsia further complicates management by exacerbating cardiovascular strain and increasing the risk of adverse outcomes for both mother and fetus. This case report highlights the importance of multidisciplinary collaboration and careful perioperative planning for pregnant women with RHD, particularly in resource-limited settings. We report the case of a 31-year-old woman (G3P2A0) at 40–41 weeks of gestation, diagnosed with severe preeclampsia, severe mitral stenosis, moderate mitral regurgitation, and severe tricuspid regurgitation due to RHD. An elective cesarean section was performed under epidural anesthesia with 0.75% ropivacaine, ensuring hemodynamic stability throughout the procedure and during a 24-hour ICU observation. Despite limited access to cardiovascular specialists and surgical options, a team-based approach and tailored anesthetic management ensured a favorable outcome. In conclusion, this case demonstrates that even in settings with constrained resources, proper planning, close monitoring, and multidisciplinary coordination can mitigate the risks associated with multivalvular heart disease and severe preeclampsia in pregnancy. Interdisciplinary collaboration and individualized anesthetic strategies are crucial for optimizing maternal and fetal outcomes in such complex scenarios.